Does the Nobel Prize reflect current scientific and academic values? - Teixeira da Silva, Jaime A. (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
This opinion paper puts forward arguments that reflect how science’s most elite prize, the Nobel Prize may be, despite its grand stature, somewhat out of touch with the functionality of grassroots science. There is a disconnect between limited fields of study to which the prize is awarded and the interdisciplinary nature of complex research. This is the first weakness. The second limitation is the focus on a single individual, occasionally on two or three when the prize is divided, even though much research is frequently collaborative. This is particularly true in the biomedical and natural sciences, which tend to involve individuals with multiple skills, each or all of whom may be equally deserving of the Nobel Prize, given their collective participation. The Nobel Prize also tends to display poor cultural, linguistic and gender representation and/or bias. Finally, retractions of papers by select Nobel Prize laureates suggest that even these elite academics are not immune to the ills of science and academic publishing and that affect all scientists in a complex global web.